APPLICATION OF VOSYS-OPTIMA SYSTEM COMPONENTS IN CONSTRUCTION OF HARDWARE LAYOUTS OF MONOLATERAL COMBINATION WITH ANGULAR SUPPORT IN CASES OF TREATMENT OF INTRAARTICULAR KNEE FRACTURES AND DISTAL CIRCUMARTICULAR FRACTURES OF THE FEMUR IN DOGS AND CATS - Igor G. Kiselev; Andrey A. Yemanov; Matvei I. Rodin (Siberian Journal of Life Sciences and Agriculture, 2023)
For treatment of prearticular and intraarticular fractures including knee joint area in dogs and cats, as a rule, thin pins, serclage, plates, and their combinations are used depending on fracture area and fracture complexity, which fails to fully provide sufficient stability of osteosynthesis.